2015
DOI: 10.3354/aei00155
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and ecological challenges of monitoring parasitic salmon lice infestations in wild salmonid fish stocks

Abstract: Ecological monitoring programmes should provide precise data to inform management, but the data quality is often limited by methodological challenges and the need for cost-effective sampling. Parasite infestations are particularly challenging to monitor due to complex interactions among hosts, parasites and the environment. In Norway, salmon lice infestations on wild salmonid fish have been monitored since 1992 to survey the potential transmission between farmed and wild salmonids. Here, we compared spatiotemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
(65 reference statements)
1
22
0
Order By: Relevance
“…Levels of lice infestation associated with salmon farms are likely to change across gradients of external stressors (e.g. Lafferty & Kuris 1999) such as temperature and rainfall (Helland et al 2015). The present study uses a large international dataset to develop statistical models describing lice infestation and body condition of sea trout.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…Levels of lice infestation associated with salmon farms are likely to change across gradients of external stressors (e.g. Lafferty & Kuris 1999) such as temperature and rainfall (Helland et al 2015). The present study uses a large international dataset to develop statistical models describing lice infestation and body condition of sea trout.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…The salinity history of the tagged fish indicated that the post-smolts occasionally spent time in sea water with lower salinity than 20.0 psu, especially in the inner part of the fjord. The utilization of salinities below 20.0 psu may reduce infestation risk by salmon lice [22,23], and the probability of infestation is generally shown to decrease with increasing freshwater influence [35]. Salmon louse is a marine parasite, which can severely reduce Atlantic salmon populations in farm-intensive areas [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In farm-intensive areas, lice levels on wild salmonids are typically higher, and more variable than in farm-free areas (e.g. Serra-Llinares et al, 2014Helland et al, 2015;Thorstad et al, 2015). The individual physiological and pathological effects of salmon lice on salmonids have been thoroughly described , and population level effects have been well documented for Atlantic salmon.…”
Section: Salmon Licementioning
confidence: 99%